Ask Question
26 June, 14:14

Use substitution or elimination

y=-2x - 6

y = x + 9

+3
Answers (1)
  1. 26 June, 15:42
    0
    y=12

    Step-by-step explanation:

    elimination method

    y=-2x - 6

    y=x•2 + 9•2

    rewrite problems

    y=-2x - 6

    y=2x + 18

    the positive and negative 2x cancels out so you are left with y=12
Know the Answer?
Not Sure About the Answer?
Find an answer to your question ✅ “Use substitution or elimination y=-2x - 6 y = x + 9 ...” in 📘 Mathematics if you're in doubt about the correctness of the answers or there's no answer, then try to use the smart search and find answers to the similar questions.
Search for Other Answers